2011
DOI: 10.1177/0192623311409597
|View full text |Cite
|
Sign up to set email alerts
|

Normal Anatomy and Histology of the Adult Zebrafish

Abstract: The zebrafish has been shown to be an excellent vertebrate model for studying the roles of specific genes and signaling pathways. The sequencing of its genome and the relative ease with which gene modifications can be performed have led to the creation of numerous human disease models that can be used for testing the potential and the toxicity of new pharmaceutical compounds. Many pharmaceutical companies already use the zebrafish for prescreening purposes. So far, the focus has been on ecotoxicity and the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
159
0
8

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 206 publications
(177 citation statements)
references
References 22 publications
10
159
0
8
Order By: Relevance
“…Other cells i.e., supporting, mucous and basal cells were also exhibited based on localization and histological characterization. This structure was similar to that of some other fishes such as P. kuhlii, P. senegalus (Genten et al 2008) and D. rerio (Menke et al 2011).…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…Other cells i.e., supporting, mucous and basal cells were also exhibited based on localization and histological characterization. This structure was similar to that of some other fishes such as P. kuhlii, P. senegalus (Genten et al 2008) and D. rerio (Menke et al 2011).…”
Section: Resultssupporting
confidence: 83%
“…Therefore, it was exclusively attracted by several researchers concerning with the morphological and histological structures (Zielinski and Hara 1988). Nonetheless, only histology is exclusively examined of olfactory organ in many teleost due to providing the microscopic organization including Scyliorhinus canicula, Polypterus senegalus, Pangio kuhlii (Genten et al 2008), Danio rerio (Menke et al 2011), Oreochromis nilotica (Chakrabarti and Ghosh 2011a) and Terapon jarbua (Chakrabarti and Ghosh 2011b). Overall research showed that olfactory organ was a paired olfactory sac.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike mammals, absence of division into hepatic lobules and phagocytic cells are features of zebrafish [7]. Furthermore, they formed a muralium duplex of cells surrounding a sinusoidal capillary.…”
Section: Macroscopy and Histologymentioning
confidence: 99%
“…In general, hepatocytes metabolise endogenous and exogenous substances; produce bile, which is subsequently directed to the gallbladder, and essential proteins of the plasma and coagulation factors; and store substances such as amino acids, lipids, glycogen, and iron [7].…”
Section: Introductionmentioning
confidence: 99%
“…A comprehensive study of the histology of the anterior gut of Sulawesi medaka fish had not been established yet al,though few studies were conducted on the anatomy and histology of zebrafish (Menke et al, 2011). Nevertheless, this research is very important to know about feeding behavior and habitat of Sulawesi medaka fish, thus providing fundamental information for further anatomical and physiological studies.…”
Section: Resultsmentioning
confidence: 99%